Sociodemographic Characteristics and Clinical Profiles of Chronic Suppurative Otitis Media Patients attended at a Tertiary Care Hospital in Bangladesh - Akter, Firoza; Khaled, Md. Saifuddin; Akhter, Farida; Khan, Md Jahangir; Yusuf, Md. Abdullah (Bangladesh Journal of Infectious Diseases, 2025)
Background: Chronic suppurative otitis media (CSOM) can occur with varied sociodemographic and clinical presentations. Objective: The purpose of the present study was to assess the sociodemographic characteristics and clinical profiles of chronic suppurative otitis media patients. Methodology: This cross-sectional study was carried in the Department of Microbiology in collaboration with the Department of ENT at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh from July 2017 to June 2018 for a period of one year. In this study, aural swab was taken from patients presented with CSOM. The details of sociodemographic characteristics and clinical profiles of chronic suppurative otitis media patients were recorded in a predesigned data sheet. Results: The mean age of the patients with bacteriological growth was 25.27±15.72 years and the peak incidence of growth was observed in the age group between 11 to 20 years. Sex wise distribution of the patients with bacteriological growth were 23.8% males and 76.2% females. Conclusion: In conclusion young age females are commonly infected with chronic suppurative otitis media. Bangladesh Journal of Infectious Diseases, December 2024;11(2):88-92